Oral Ornaments: An Overview - Rajneesh Parimoo; Baljeet Singh; Divya Sharma; Vanshika Sharma; Aquib Javaid (International Healthcare Research Journal, 2020)
Nowadays, people desire to look attractive and have become very alert about their appearance and smile. Since the face is most exposed part of our body, and mouth a prominent feature, teeth are getting enormous share of attention. Intraoral jewellery has currently gained popularity and is slowly becoming a craze, but this fashion trend is also associated with some significant health issues. These ornaments though are said to enhance beauty cause problems such as increase pain, infection, scar formation, tooth fractures, metal hyper-sensitivity reactions, localized periodontal disease, speech impediment, and nerve damage. This review draws special attention to the prevalence, complications, and side effects of dental jewellery in humans. Here we suggest people must be aware of all the risks associated with wearing dental jewellery, and they should undergo dental check-ups regularly.